The Slotted Antler Points from Trail Creek Caves, Alaska: New Information on Their Age and Technology. (2nd January 2016) - Lee, Craig; Goebel, Ted
Abstract : Despite their occurrences in Siberian and Alaskan late Pleistocene and early Holocene archaeological sites, we know little about the temporal and geographic variability of slotted osseous projectile points. Here we present the results of an analysis of seven slotted antler points from Trail Creek Cave 2 on the Seward Peninsula in western Alaska. The points are morphologically uniform in that they are small and symmetrical. Three concordant AMS 14 C radiocarbon ages obtained on gelatin with calibrated median probabilities ranging from 11, 350 to 11, 257 calendar years ago suggest their manufacture and use during the earliest Holocene. A fourth point yielded a calibrated median probability of 10, 335 calendar years ago, suggesting the cave saw reuse, which is consistent with Helge Larsen's original contention. The analysis provides a benchmark for understanding the temporal context of the small form of slotted points found in Alaska's early record, which are often referred to as 'arrowheads'.